Comparative Long-Term Effect of Three Anti-P2Y12 Drugs after Percutaneous Angioplasty: An Observational Study Based on Electronic Drug Adherence Monitoring - Forni Ogna, Valentina; Bassi, Isabelle; Menetrey, Isabelle; Muller, Olivier; Tousset, Eric; Fontana, Pierre; Eeckhout, Eric; Eap, Chin B.; Vrijens, Bernard; Burnier, Michel; Wuerzner, Grégoire (Frontiers in Pharmacology, 2017)
Aims: Dual platelet inhibition using anti-P2Y12 drugs and aspirin is the standard of care in patients after percutaneous coronary interventions (PCI). Prasugrel and ticagrelor have been shown to be more potent than clopidogrel with less high on-treatment platelet reactivity. Whether differences in long-term adherence to these drugs can partly explain different antiplatelet efficacy has not been studied so far. The objective was to compare the long-term P2Y12 receptor inhibition and drug adherence to different anti-P2Y12 drugs, and to assess the impact of adherence on the pharmacodynamic effect. Methods: Monocentric, prospective, observational study. Stable outpatients treated with clopidogrel 75 mg once daily, prasugrel 10 mg once daily or ticagrelor 90 mg twice daily after PCI with stent implantation were included. Drug adherence was recorded during 6 months using electronic monitoring. Platelet responsiveness was assessed with the vasodilator-stimulated phosphoprotein platelet reactivity index (VASP-PRI) at inclusion, 3 and 6 months. Results: 120 patients had VASP-PRI and adherence data available. At 6-months, mean VASP-PRI (±SD) was 17.7 ± 11.0% with ticagrelor, 29.2 ± 15.5% with prasugrel and 47.2 ± 17.6% with clopidogrel (ANOVA, P < 0.0001). Median [IQR] taking adherence was 96 [82–100]% with ticagrelor, 100 [97–101]% with prasugrel and 100 [99–101]% with clopidogrel (p = 0.0001). Median [IQR] correct dosing was 88 [73–95]% with ticagrelor, 97 [92.5–98]% with prasugrel and 98 [96–99]% with clopidogrel (p = 0.0001). Anti-P2Y12 drug (p ≤ 0.001) and diabetes (p = 0.014) emerged as predictors of poor antiplatelet response after adjusting for age, BMI, sex, and CYP2C19∗2 carriers status. Conclusion: Drug adherence to anti-P2Y12 drugs assessed with electronic monitoring was very high. However, anti-P2Y12 drugs showed significant differences in antiplatelet activity, with newer anti-P2Y12 drugs ticagrelor and prasugrel exerting a stronger P2Y12 receptor inhibition. These data suggest that pharmacokinetic-pharmacodynamic differences between oral anti-P2Y12 drugs are more important than adherence in determining antiplatelet efficacy when adherence to prescription is high. The study was registered (Current Controlled Trials ISRCTN85949729).